THE CORRELATION BETWEEN ENGLISH GRAMMAR COMPETENCE AND SPEAKING FLUENCY - Siska Anisa Kusumawardani; Endah Mardiyani (PROJECT (Professional Journal of English Education), 2018)
The objective in this case to examine how English grammar competence can influence speaking fluency. The authorcharity quantitative method, and correlation research design. The population was 170 of tenth grade students from 6 classes, at MAN Cimahi in academic year 2018/2019 and the sample was 34 students from design class. The instruments took grammar test and speaking interview. The student’s grammar competence scores (X) and the student’s speaking fluency (Y) were analysed and it is found that the distribution of data is not normal. The result of data analysis showed that correlation coefficient (r) equals to 0.259, larger than social significance value which is 0.05. the interpretation of the relationship is weak correlation. The Null hypothesis is accepted.Keywords:Grammar Competence, Speaking Fluency